I'm not like everybody else : biopolitics, neoliberalism, and American popular music - Nealon, Jeffrey T. (Jeffrey Thomas) (Provocations (Lincoln, Neb.), 2018)
Despite the presence of the Flaming Lips in a commercial for a copier and Iggy Pop's music in luxury cruise advertisements, the author argues that popular music has not exactly been co-opted in the American capitalist present. Contemporary neoliberal capitalism has, in fact, found a central organizing use for the values of twentieth-century popular music: being authentic, being your own person, and being free. In short, not being like everybody else. Through a consideration of the shift in dominant modes of power in the American twentieth and twenty-first centuries, from what Michel Foucault calls a dominant "disciplinary" mode of power to a "biopolitical" mode, the author argues that the modes of musical "resistance" need to be completely rethought and that a commitment to musical authenticity or meaning - saying "no" to the mainstream - is no longer primarily where we might look for music to function against the grain